(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The following paper willfocus on some of the major new perspectives on the Indus Civilization that arethe result of new discoveries at sites in both the core regions of the IndusCivilization that are found in Pakistan and India. New research in adjacentregions are also revealing evidence of ancient interactions between the Indusregion and the territories of modern Afghanistan, Turkmenistan, Iran, Oman, theUnited Arab Emirates, Bahrain, Kuwait, Iraq, Syria, and even further afield. Afew of these important discoveries will be discussed to highlight thechallenges that we face in understanding the complex networks of exchange andinteraction that were present in the 3,d millennium BCE.